Service State Institutionalization in the Social Transformations Context - Popov, Vitaly V.; Muzyka, Oksana A.; Semenova, Veronika G.; Agafonova, Tatiyna V.; Samoylova, Irina N.; Timofeenko, Veronika A. (International Journal of Psychosocial Rehabilitation, 2020)
Purpose – The aim of the work is to demonstrate that in studies of social and economic transformations within the framework of a transitive society, it is advisable to conduct a discourse that reinforcing individualization, consumer demands, needs, values, which are the motives of consumption and form a new approach to servicing, called “service”. Design/Methodology/Approach – The general philosophical methods and principles of research are historical, concrete, systematic, comprehensive, unity of concrete and abstract, logical and historical in social cognition, as well as such social and philosophical methods as analogy, modeling, comparative-historical and historical retrospective. Findings – Summarizing various conceptual developments, we consider it expedient to define the “service state” as a special socio-political form of organization of state power, which has a special administrative apparatus whose activity is aimed at providing public services, as well as a system of socio-economic and political-legal guarantees of rights and freedoms of man and citizen. Practical Implications – The results of the work are of practical importance in that the service approach to the system of public administration and the network methodology for improving managerial activity can correct the shortcomings of the bureaucratic management style; eliminate corrupt systemic defects and practical problems of interaction between the state and society Originality/Value – The article makes one of the first attempts to show the features of the “service approach” in public administration that predetermines the transition from “binding” to “providing” public administration. In this connection, the social essence of the modern state is based on the provision of high-quality public services.